Coupling Ifosfamide to nanoemulsion-based clove oil enhances its toxicity on malignant breast cancer and cervical cancer cells - Sahar M. AlMotwaa (Pensoft Publishers, 2021)
The anticancer effects of chemotherapeutic agents may be accentuated, and their side effects minimized by combining them with essential oils in nanocarrier systems. This study aimed to incorporate ifosfamide (IF) into nanoemulsion-based clove oil (IF-CLV). The nano-emulsion (NE) formulas were characterized with Zetasizer. The cytotoxicity of the formulated NEs against cervical (HeLa) and breast (MCF-7) cancer cell lines was determined using MTT assay, light microscopy, and DAPI staining. The z - average diameters of NE-CLV and IF-CLV were 63.1±1.00 and 89.4±2.64 nm, while Zeta potential values were - 4.39±0.4 and - 11.65±1.1mV, respectively. Cytotoxicity studies revealed that relative to free IF, NE-CLV and IF-CLV were highly toxic on HeLa and MCF-7cells, in a dose-dependent manner. The half-maximal inhibitory concentration (IC50) values of NE-CLV against HeLa and MCF-7 have decreased 38 and 27 folds, while the corresponding IC50 values of IF-CLV have decreased 57 and 35 folds, respectively. These results suggest that the incorporation of IF into NE-based clove oil produces potent therapeutic effects against cancer cell lines.